The Development of Gus Dur’s Pluralism Thought (1971-2001) - Nadif Hanan Narendra; Hieronymus Purwanta; Nur Fatah Abidin (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2022)
Gus Dur is well acknowledge as pluralists. The problem this research is how Gus Dur's thoughts on pluralism from 1971 to 2001. This article aims to analyze the development of Gus Dur's thoughts on pluralism from 1971 to 2001. This research used historical method. The research findings show that Gus Dur's thoughts on pluralism were influenced by internal and external factors. According to Gus Dur, pluralism focuses on monotheism, law (fiqh), and ethics (akhlaq). This policy often caused controversy, however, Gus Dur's policy of pluralism was able to eliminate the influence of the New Order, restore the human rights of victims of discrimination such as victims who were considered involved in the communist party and ethnic Chinese, as well as resolve the problems of separatism that occurred in Indonesia. Gus Dur's thought of pluralism was formed based on Gus Dur's dialectic with the surrounding environment from his school days to serving as president. Although it generates controversy, Gus Dur's thinking of pluralism has opened the nation's horizons regarding the good practice of pluralism that needs to be continued in the current era.